Diseño de un modelo logístico de entrada para una red de valor en el sector textil y de confección en Bogotá D.C. (2019)
The research aims to support this sector to Through the design of an entry logistic model for its value network Identifying the main activities such as supply, management of inventories, order management and the organizations that create a The competitive advantage and the contribution to the development of the sector. The creation of this model began with a state of the art through consultation. and the collection of data in secondary sources. Books, magazines, theses, documents, among others; key process to identify the Incident causes in the real and subsequent sector. from the same. The above is equivalent to the base of the project which is based on the methodology of the intellectual model and the generic configuration of the network to value as a result The logistic entry model for a value network in the textile and Confecciones, creating an opportunity not only for the sector but also for the Colombian manufacturing industry.